Benefits of automated gross tumor volume segmentation in head and neck cancer using multi-modality information. (May 2023) - Bollen, Heleen; Willems, Siri; Wegge, Marilyn; Maes, Frederik; Nuyts, Sandra
Abstract: Purpose: Gross tumor volume (GTV) delineation for head and neck cancer (HNC) radiation therapy planning is time consuming and prone to interobserver variability (IOV). The aim of this study was (1) to develop an automated GTV delineation approach of primary tumor (GTVp) and pathologic lymph nodes (GTVn) based on a 3D convolutional neural network (CNN) exploiting multi-modality imaging input as required in clinical practice, and (2) to validate its accuracy, efficiency and IOV compared to manual delineation in a clinical setting. Methods: Two datasets were retrospectively collected from 150 clinical cases. CNNs were trained for GTV delineation with consensus delineation as ground truth, with either single (CT) or co-registered multi-modal (CT + PET or CT + MRI) imaging data as input. For validation, GTVs were delineated on 20 new cases by two observers, once manually, once by correcting the delineations generated by the CNN. Results: Both multi-modality CNNs performed better than the single-modality CNN and were selected for clinical validation. Mean Dice Similarity Coefficient (DSC) for (GTVp, GTVn) respectively between automated and manual delineations was (69%, 79%) for CT + PET and (59%, 71%) for CT + MRI. Mean DSC between automated and corrected delineations was (81%, 89%) for CT + PET and (69%, 77%) for CT + MRI. Mean DSC between observers was (76%, 86%) for manual delineations and (95%, 96%) for corrected delineations, indicating a significant decrease in IOV (p < 10 −5 ), while efficiency increased significantly (48%, p < 10 −5 ). Conclusion: Multi-modality automated delineation of GTV of HNC was shown to be more efficient and consistent compared to manual delineation in a clinical setting and beneficial over a single-modality approach.